Implementasi Mobilisasi Dini pada NY. M G2P2A0 dengan Gangguan Mobilitas Fisik Post Partum Sectio Caesarea di Ruang Dewi Sartika RSUD Arjawinangun Kabupaten Cirebon - Nengsih Yulianingsih; Desi Indriani (NAJ Nursing Applied Journal, 2025)
Background: A Caesarean section (CS) is a birthing procedure performed by making an incision in the mother's abdominal wall and uterus to deliver the baby, usually performed when normal vaginal delivery is not possible due to medical indications for the mother or fetus, such as placenta previa, abnormal presentation or position of the fetus, and other conditions that pose a risk of medical complications that endanger the mother and fetus. At Arjawinangun Regional Hospital, 1,491 CS births were recorded in 2021. One of the problems that often occurs in post-Cesarean section patients is impaired physical mobility, which causes limitations in the ability to move independently. This disorder needs to be addressed immediately so as not to hinder the recovery process. To overcome this problem, early mobilization intervention is very important. Early mobilization is a way to help patients increase their physical activity after undergoing surgery. Objective: This study aims to determine the description of the implementation of early mobilization in Mrs. M with impaired physical mobility after Caesarean section in the Dewi Sartika room, Arjawinangun Regional Hospital, Cirebon Regency, and to assess its effectiveness in overcoming these impaired physical mobility. Implementation method: This study used a case study method with research subjects in the form of patients who experienced impaired physical mobility after Sectio Caesarea at RSUD Arjawinangun Cirebon Regency. The implementation process involved providing early mobilization instructions which included light movement exercises tailored to the patient's condition. Results: The results of the study showed that after the implementation of early mobilization, impaired physical mobility in patients after Sectio Caesarea could be resolved significantly. Patients showed increased ability to move, reduced pain, and accelerated the post-operative recovery process.